Role of Intestinal LXRα in Regulating Post-prandial Lipid Excursion and Diet-Induced Hypercholesterolemia and Hepatic Lipid Accumulation - Tibiábin Benítez-Santana; Tibiábin Benítez-Santana; Sarah E. Hugo; Sarah E. Hugo; Amnon Schlegel; Amnon Schlegel; Amnon Schlegel; Amnon Schlegel (Frontiers in Physiology, 2017)
Post-prandial hyperlipidemia has emerged as a cardiovascular risk factor with limited therapeutic options. The Liver X receptors (Lxrs) are nuclear hormone receptors that regulate cholesterol elimination. Knowledge of their role in regulating the absorption and handling of dietary fats is incomplete. The purpose of this study was to determine the role of intestinal Lxrα in post-prandial intestinal lipid transport. Using Lxrα knockout (nr1h3−/−) and intestine-limited Lxrα over-expressing [Tg(fabp2a:EGFP-nr1h3)] zebrafish strains, we measured post-prandial lipid excursion with live imaging in larvae and physiological methods in adults. We also conducted a long-term high-cholesterol dietary challenge in adults to examine the chronic effect of modulating nr1h3 gene dose on the development of hypercholesterolemia and hepatic lipid accumulation. Over-expression of Lxrα in the intestine delays the transport of ingested lipids in larvae, while deletion of Lxrα increases the rate of lipid transport. Pre-treating wildtype larvae with the liver-sparing Lxr agonist hyodeoxycholic acid also delayed the rate of intestinal lipid transport in larvae. In adult males, deletion of Lxrα accelerates intestinal transport of ingested lipids. Adult females showed higher plasma Lipoprotein lipase (Lpl) activity compared to males, and lower post-gavage blood triacylglycerol (TAG) excursion. Despite the sexually dimorphic effect on acute intestinal lipid handling, Tg(fabp2a:EGFP-nr1h3) adults of both sexes are protected from high cholesterol diet (HCD)-induced hepatic lipid accumulation, while nr1h3−/− mutants are sensitive to the effects of HCD challenge. These data indicate that intestinal Lxr activity dampens the pace of intestinal lipid transport cell-autonomously. Selective activation of intestinal Lxrα holds therapeutic promise.